Culture and community perceptions on diet for maternal and child health: a qualitative study in rural northern Ghana - Maxwell A. Dalaba; Engelbert A. Nonterah; Samuel T. Chatio; James K. Adoctor; Daniella Watson; Mary Barker; Kate A. Ward; Cornelius Debpuur (BMC Nutrition, 2021)
Abstract Background This study explored cultural and community perceptions of optimal diet for maternal and child health in northern Ghana. Methods This was an exploratory cross-sectional study using qualitative methods for data collection. Data were collected between March and April 2019 consisting of 10 focus group discussions with men and women community members between 18 and 50 years in the Kassena-Nankana districts of Ghana. Data were organised using QSR NVivo 12 qualitative software to facilitate thematic analysis. Results All study participants recognised the importance of an optimal diet for mother, child and better pregnancy and breastfeeding outcomes. However, there were different cultural beliefs and taboos about what foods are healthy and non-healthy for women at different stages of the reproductive period. Foods perceived to be unhealthy for pregnant women were fatty foods and fresh meat (uncooked or unprocessed meat) due to the belief that they can lead to delivery complications, which many women feared. In addition, some participants relayed the cultural belief that pregnant woman should not eat eggs because it would make the child a thief. Lactating mothers are not to eat foods such as vigna subterranean known locally as bambara bean and “gari” (local meal made from cassava) because it is believed to inhibit breastmilk production. Participants emphasised that food insecurity and economic constraints meant women could not achieve optimal diet and could not afford to be selective in food choices. Conclusion Community members recognized the importance of optimal nutrition but were constrained by poverty and cultural barriers. A dual approach which targets improvements of local food production and economic empowerment in combination with community-based discussion and education of the impacts of food taboos on health, should facilitate improvement in the diets of women and future generations.